The Prohibition Language Style and Its Meanings in The Noble Quran Surah Al-Maidah/ أساليب النهي ومعانيها في القرآن الكريم سورة المائدة - Ratu Madaniyyah; Shafruddin Tajuddin; Muhammad Kamal bin Abdul Hakim (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2022)
This study aimed to get a clear description of The Prohibition Language Style and Its Meanings or Purposes in The Noble Quran Surah Al-Maidah. This study is an analysis of literature research using the qualitative descriptive method with the content analysis. the result of Prohibition Language Style and Its Meanings or Purposes in The Noble Quran Surah Al-Maidah is as follows: There are 21 findings of the prohibition language style in 16 verses and they are in verses 2, 3, 8, 21, 26, 41, 44, 48, 49, 51, 57, 68, 77, 87, 95, 101. Each verse consists of real and figurative meaning. The real meanings are 6 findings in 5 verses and the figurative meaning are 15 findings in 14 verses. These figurative meanings consist of 5 meanings, that is (1) The meaning of threat has 6 findings in 5 verses, (2) The meaning of tranquility has 5 findings in 5 verses, (3) The meaning of reproach has 2 findings in 2 verses, (4) The meaning of hatred has 1 finding in 1 verse, (5) The meaning of advice and guidance has 1 finding in 1 verse. يهدف هذا البحث إلى الحصول على معرفة أساليب النهي ومعانيها أو أغراضها في القرآن الكريم سورة المائدة. وإن هذا البحث من ضمن الدراسة المكتبية باستخدام الطريقة الوصفية بأسلوب تحليل المحتوى. فنتيجة البحث عن أساليب النهي في سورة المائدة هي يوجد 21 شاهدا من أسلوب النهي في 16آية وهي في آية 2، 3، 8، 21، 26، 41، 44، 48، 49، 51، 57، 68، 77، 87، 95، 101. وكلها تتكون من المعنى الحقيقي والمعنى المجازي. وتكون المعاني الحقيقية في 6 شواهد وذلك في 5 آيات. وتكون المعاني المجازية في 15 شاهدا وذلك في 14 آية. تتكون هذه المعاني المجازية في 5 معان وهي: (1) التهديد في 6 شواهد وهي في 5 أيات، (2) الائتناس في 5 شواهد وهي في 5 آيات، (3) التوبيخ في شاهدين وهي في آيتين، (4) الكراهة في شاهد واحد وفي آية واحدة، (5) النصح والإرشاد في شاهد واحد وفي آية واحدة.